Galleria mellonella as an Infection Model for Bacillus anthracis Sterne - Malmquist, Jacob A.; Rogan, Madison R.; McGillivray, Shauna M. (Frontiers in Cellular and Infection Microbiology, 2019)
Understanding bacterial virulence provides insight into the molecular basis behind infection and could identify new drug targets. However, assessing potential virulence determinants relies on testing in an animal model. The mouse is a well-validated model but it is constrained by the ethical and logistical challenges of using vertebrate animals. Recently the larva of the greater wax moth Galleria mellonella has been explored as a possible infection model for a number of pathogens. In this study, we developed G. mellonella as an infection model for Bacillus anthracis Sterne. We first validated two different infection assays, a survival assay and a competition assay, using mutants containing disruptions in known B. anthracis virulence genes. We next tested the utility of G. mellonella to assess the virulence of transposon mutants with unknown mutations that had increased susceptibility to hydrogen peroxide in in vitro assays. One of these transposon mutants also displayed significantly decreased virulence in G. mellonella. Further investigation revealed that this mutant had a disruption in the petrobactin biosynthesis operon (asbABCDEF), which has been previously implicated in both virulence and defense against oxidative stress. We conclude that G. mellonella can detect attenuated virulence of B. anthracis Sterne in a manner consistent with that of mammalian infection models. Therefore, G. mellonella could serve as a useful alternative to vertebrate testing, especially for early assessments of potential virulence genes when use of a mammalian model may not be ethical or practical.